Genealogy in the System of Modern Knowledge: Theory and Methodology of Cognitive History of O.M. Medushevskaya - Irina V. Sabennikova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2024)
The author analyzes the place of genealogy as a unique indicator of humanitarian culture both in historical retrospect and modern society, since the subject of its study has traditionally been universal human values - family, kinship and relationships between different generations. The purpose of the article is to show the role of famous historian O.M. Medushevskaya and the significance of the theory and methodology of cognitive history developed by her for determining the place of genealogy in the system of modern knowledge. In the article, within the framework of this theory the place of genealogy in the system of modern knowledge is determined; the author gives a clear definition of the subject area of genealogy as a sphere of research, the possibility of interdisciplinary synthesis with a number of fundamental sciences, and formulates a program for the development of this field of knowledge in Russia. The author comes to the conclusion that the approach developed by O.M. Medushevskaya transforms genealogy from an auxiliary and applied discipline into one of the central areas of humanitarian-historical knowledge, making it an information resource for studying the history of family and clan, economic history (movement of property), the socio-political structure of society (or the history of classes), culture and its individual representatives.